2018
DOI: 10.1111/tbed.12888
|View full text |Cite
|
Sign up to set email alerts
|

First isolation of West Nile virus in Zambia from mosquitoes

Abstract: Mosquito surveillance studies to identify mosquito-borne flaviviruses have identified West Nile Virus (WNV) for the first time in Zambia. The Zambian WNV isolate from Culex quinquefasciatus mosquitoes collected in the Western Province was closely related genetically to WNV lineage 2 South African strains which have been previously shown to be highly neuroinvasive. These data provide the first evidence of the circulation of WNV in Zambia and suggest there should be an increased awareness of possible associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 16 publications
1
33
0
1
Order By: Relevance
“…Recently, antibodies specific to ZIKV were also detected in non-human primates in Zambia [29]. Furthermore, our mosquito surveillance studies have shown that the first evidence of the circulation of WNV and the existence of a novel alphavirus in Zambia [30,31].…”
Section: Introductionmentioning
confidence: 79%
“…Recently, antibodies specific to ZIKV were also detected in non-human primates in Zambia [29]. Furthermore, our mosquito surveillance studies have shown that the first evidence of the circulation of WNV and the existence of a novel alphavirus in Zambia [30,31].…”
Section: Introductionmentioning
confidence: 79%
“…Although mosquitoes are not competent vectors for BTV, the incidental detection of BTV nucleic acid from a blood-engorged pool collected from Western Province of Zambia [31] supports the idea of a potential role of mosquitoes in the epidemiology of BT [32,33]. Detection of BTV nucleic acid and antibodies in indigenous cattle and goats in eight provinces (i.e., Eastern, Copperbelt, Southern, Northern, Muchinga, Western, and Lusaka and Central) indicates widespread distribution of BT in Zambia.…”
Section: Discussionmentioning
confidence: 99%
“…RNA was extracted from individual pools and subjected to a pan flavivirus RT-PCR to detect WNV, dengue virus, and yellow fever virus (YFV). Two pools of Culex mosquitoes which were collected during 2016 were positive for WNV using RT-PCR [82]. Sequencing and phylogenetic analysis revealed that the sequences belonged to the WNV lineage 2 strain, which was the first report of this virus from Zambia [82].…”
Section: Zambiamentioning
confidence: 95%
“…Two pools of Culex mosquitoes which were collected during 2016 were positive for WNV using RT-PCR [82]. Sequencing and phylogenetic analysis revealed that the sequences belonged to the WNV lineage 2 strain, which was the first report of this virus from Zambia [82]. Intriguingly, a recent serological investigation reported that some human individuals had antibodies against WNV, which pointed towards the circulation of WNV in the country [83].…”
Section: Zambiamentioning
confidence: 98%
See 1 more Smart Citation